2020
DOI: 10.1186/s13018-020-01913-1
|View full text |Cite|
|
Sign up to set email alerts
|

A new 3D printing porous trabecular titanium metal acetabular cup for primary total hip arthroplasty: a minimum 2-year follow-up of 92 consecutive patients

Abstract: Background: Aseptic cup loosening is still one of the main reasons leading to acetabular cup failures. 3D printing porous trabecular titanium metal acetabular cup may provide good initial stability and secondary fixation because of its highly interconnected, porous structure. Few large sample studies have reported the clinical outcomes of electron beam melting (EBM) porous titanium acetabular cup in Chinese population. Methods: We retrospectively collected and analyzed the clinical data of a total of 92 consec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The outcomes of 3D printed ACT sockets were retrospectively assessed in 108 hips by Geng et al [ 26 ] at an average follow-up of 48 months. A significant clinical improvement was observed, with 106 of 108 (91.3%) patients satisfied with the outcome.…”
Section: Clinical and Radiological Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of 3D printed ACT sockets were retrospectively assessed in 108 hips by Geng et al [ 26 ] at an average follow-up of 48 months. A significant clinical improvement was observed, with 106 of 108 (91.3%) patients satisfied with the outcome.…”
Section: Clinical and Radiological Outcomesmentioning
confidence: 99%
“…Radiographic signs of osseointegration were evident in all the cups. The overall survival rate was 99.1% at 72 months, with cup survival rate achieving 100%[ 26 ].…”
Section: Clinical and Radiological Outcomesmentioning
confidence: 99%
“…The application of 3D printing in primary joint arthroplasty is mainly realized by designing osteotomy guide plates [ 8 ] and customizing personalized prostheses [ 9 , 10 ]. A series of clinical studies have shown that 3D printing technology can achieve excellent clinical outcomes [ 11 13 ]. With the further development of the research, orthopedic surgeons are using 3D printing technology to assist in RTHA and revision total knee arthroplasty (RTKA), especially for complex revision surgery involving bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials, also called cellular solids, fabricated by additive manufacturing have attracted attention in biomedical implants, such as acetabular hip cups [ 1 , 2 , 3 ], mandibles [ 4 ], fusion cages [ 5 , 6 ], and various other applications [ 2 ]. Implants made from a material with a low elastic modulus can reduce the effect of stress shielding [ 7 ].…”
Section: Introductionmentioning
confidence: 99%